Partners at Care Transitions: exploring healthcare professionals' perspectives of excellence at care transitions for older people. Issue 9 (19th September 2018) - Baxter, Ruth; O'Hara, Jane; Murray, Jenni; Sheard, Laura; Cracknell, Alison; Foy, Robbie; Wright, John; Lawton, Rebecca
Abstract : Introduction: Hospital admissions are shorter than they were 10 years ago. Notwithstanding the benefits of this, patients often leave hospital requiring ongoing care. The transition period can therefore be risky, particularly for older people with complex health and social care needs. Previous research has predominantly focused on the errors and harms that occur during transitions of care. In contrast, this study adopts an asset-based approach to learn from factors that facilitate safe outcomes. It seeks to explore how staff within high-performing ('positively deviant') teams successfully support transitions from hospital to home for older people. Methods and analysis: Six high-performing general practices and six hospital specialties that demonstrate exceptionally low or reducing 30-day emergency hospital readmission rates will be invited to participate in the study. Healthcare staff from these clinical teams will be recruited to take part in focus groups, individual interviews and/or observations of staff meetings. Data collection will explore the ways in which teams successfully deliver exceptionally safe transitional care and how they overcome the challenges faced in their everyday clinical work. Data will be thematically analysed using a pen portrait approach to identify the manifest (explicit) and latent (abstract) factors that facilitate success. Ethics and dissemination: Ethical approval was obtained from the University of Leeds. The study will help develop our understanding of how multidisciplinary staff within different healthcare settings successfully support care transitions for older people. Findings will be disseminated to academic and clinical audiences through peer-reviewed articles, conferences and workshops. Findings will also inform the development of an intervention to improve the safety and experience of older people during transitions from hospital to home.